Review: Henry James’s enigmas: Turning the screw of eternity? (Nouvelle poétique comparatiste. Vol. 31. Directeur de collection: Marc Maufort.) By Jean Perrot. Peter Lang: Bruxelles, Bern, Berlin, Frankfurt am Main, New York, Oxford, Wien, 2014. 309 pp., 1 ill. - Buchholtz, Miroslawa (Studia Anglica Posnaniensia, 2015)
Review: Henry James’s enigmas: Turning the screw of eternity? (Nouvelle poétique comparatiste. Vol. 31. Directeur de collection: Marc Maufort.) By Jean Perrot. Peter Lang: Bruxelles, Bern, Berlin, Frankfurt am Main, New York, Oxford, Wien, 2014. 309 pp., 1 ill.